Parámetros prudenciales de liquidez inmediata y estructural de las Cooperativas De Ahorro y Crédito Once De Junio y Santa Rosa. - Ayala Cordova, Gina Elizabeth (My University, 2019)
During the last two decades Ecuadorian financial institutions have suffered from serious episodes linked to the lack of liquidity, a situation that has compromised and has put at risk the economic stability of the country and therefore its development, among these the banking crisis of the year is remembered. 1999, systemic eventuality that lapidated the sucre and inevitably led to the adoption of dollarization; consequently, and in order to avoid the repetition of future events of similar magnitude, the Monetary and Financial Organic Code was created, which entered into force on September 12, 2014, with the purpose of regulating and protecting the monetary and financial system of the State, as well as taking care of the due sustainability of the securities and insurance regime among others; for the citizen benefit. The present investigative work is developed under a quantitative-qualitative approach; whose main objective will be to apply the prudential parameters of Immediate and Structural Liquidity on the liquidity funds of the credit cooperative Eleven de Junio and Santa Rosa, private financial institutions, belonging to the city of Machala, province of El Oro; in adherence to article 189 of the COMYF; the applied methods correspond to the Descriptive Method, and Inductive-Deductive, in conclusion the information obtained from the prudential criteria will be collated in order to determine the financial health on the liquidity indices of the pre-empted entities.
Durante las dos últimas décadas las entidades financieras ecuatorianas han sufrido de graves episodios vinculadas a la falta de liquidez, situación que ha comprometido y ha puesto en riesgo la estabilidad económica del país y por ende su desarrollo, entre estas se recuerda la crisis bancaria del año 1999, eventualidad sistémica que lapido al sucre y conllevo ineludiblemente a la adopción de la dolarización; en consecuencia y para evitar el que se repita eventos futuros de similar magnitud, se gestó el Código Orgánico Monetario y Financiero el mismo que entro en vigencia el 12 de septiembre del año 2014, con el propósito de regular y proteger el sistema monetario y financiero del Estado, así como el cuidar de la debida sostenibilidad del régimen de valores y seguros entre otros; para el beneficio ciudadano. El presente trabajo investigativo se desarrolla bajo un enfoque cuantitativo-cualitativo; cuyo objetivo principal consistirá en aplicar los parámetros prudenciales de Liquidez Inmediata y Estructural sobre los fondos de liquidez de la cooperativa de ahorro y crédito Once de Junio y Santa Rosa, instituciones financieras privadas, pertenecientes a la ciudad de Machala provincia de El Oro; en apego del artículo 189 del COMYF; los métodos aplicados corresponden al Método Descriptivo, e Inductivo- Deductivo, en conclusión se cotejara la información obtenida de los criterios prudenciales a fin de determinar la salud financiera sobre los índices de liquidez de las entidades prenombradas.
Keywords: ENTIDADES FINANCIERAS; LIQUIDEZ; LIQUIDEZ INMEDIATA; LIQUIDEZ ESTRUCTURAL; COOPERATIVAS DE AHORRO Y CRÉDITO